2003
DOI: 10.1111/j.1471-0528.2003.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

WHO multinational study of three misoprostol regimens after mifepristone for early medical abortion. I: Efficacy

Abstract: For amenorrhoea length > or =57 days, vaginal misoprostol is more effective than oral when continued with 0.4 mg oral misoprostol twice daily for seven days. Misoprostol continuation improved the efficacy in this amenorrhoea group compared with a single dose of vaginal misoprostol on day three, but it did not shorten the duration of bleeding. No differences in efficacy were observed when amenorrhoea length was < 57 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 19 publications
1
26
0
1
Order By: Relevance
“…18 This is likely to be due to the fact that several of the participating centres do not provide medical abortion routinely because mifepristone has not been licensed in their country. Experienced providers report higher complete abortion rates than those with less experience.…”
Section: Discussionmentioning
confidence: 99%
“…18 This is likely to be due to the fact that several of the participating centres do not provide medical abortion routinely because mifepristone has not been licensed in their country. Experienced providers report higher complete abortion rates than those with less experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, in termination of early pregnancy, after pretreatment with mifepristone, vaginal administration of misoprostol results in better efficacy. 1,2 We wanted to study whether the frequency of side effects in vaginal use differs from that in oral use.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper, we reported comparisons of the abortifacient efficacy, timing of expulsion and the duration of bleeding between the three regimens. 2 In this paper, we compare the detailed side effect profiles and women's perceptions of the treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol can be administered both orally or vaginally, however gastrointestinal side effects with oral administration are more [7]. In a study it has been observed that for amenorrhoea of > 57 days, vaginal misoprostol is more effective than oral administration, however no difference in efficacy was observed when amenorrhoea was < 57 days [8]. In our …”
Section: Discussionmentioning
confidence: 50%